Power Pack : end of the rainbow - Sumerak, Marc (Power Pack series, 2006)
Julie, upset by her brother's bossy attitude, decides to quit the Power Pack team, but she finds she cannot ignore the pull of family and responsibility when her three siblings are captured by the lizard-like Snark and a super-powered thief.